Influence of chromium source on plasma non-esterified fatty acid concentrations in growing-finishing pigs - C N Groesbeck; K R Lawrence; F Valdez; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
A total of 150 pigs (PIC, initial body weight 178.9 ± 14.7 lb) were used in a 35-d study to evaluate the effect of chromium propionate and chromium tripicolinate on plasma non-esterifed fatty acids (NEFA) in growing-finishing pigs. Our objective was to determine if differences between sources and rate of source being fed can be detected in fasted growing-finishing pigs by measuring plasma NEFA. Pigs were randomly allotted to one of the five dietary treatments arranged as a 2 × 2 factorial plus negative control (no chromium). Main effects were source of chromium (chromium propionate and chromium tripicolinate) and chromium concentration (100 or 200 ppb). On d 34, feeders were removed from pens 16 h before collecting blood on d 35 for analysis of plasma NEFA. There were no interactions (P>0.10) observed for chromium source, rate, or gender. There was no effect observed (P>0.10) of chromium source or rate on ADG, ADFI, or F/G. There was no chromium-source effect (P>0.73) observed for NEFA, but there was a tendency (quadratic, P>0.08) for plasma NEFA to decrease in pigs fed 100 ppb chromium tripicolinate and to increase in the pigs fed 200 ppb tripicolinate.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Chromium propionate; Chromium tripicolinate; NEFA; Pigs; Swine